PERTANIAN KONVENSIONAL DAN PUPUK ORGANIK : IMPLEMENTASI PROGRAM UNIT PENGOLAH PUPUK ORGANIK (UPPO) DI KELOMPOK TANI SILIH ASIH - Asri Nurrizka Hendarliana; Mahra Arari Heryanto; Ronnie Susman Natawidjaja; Pandi Pardian (Universitas Galuh Ciamis, 2021)
The negative impact of the green revolution for the agriculture sector is soil damageand pest population. The government issued an organic farming program using the SRI and UPPO method. The Silih Asih Farmers Group implements manure pasan effprt to approach organic rice farming with the aim of increase soil looseness so the productivity can increase and be stable. However, UPPO activities have not developed since 2016 due to changes in the business concept applied. The aims of this research include : 1). Knowing the reason UPPO is not growing, 2). What factors caused UPPO not to develop. The method used in this study is a qualitative method using a system thinking and Participatory Rural Appraisal (PRA) approach. The analytical tool usesd is vensim as well as a chart of changes and trends. The results of this study are: 1). UPPO of the Silih Asih farmer group did not develop because of a change in business so that the livestock population did not increase, 2). Factors that may hinder the development of a UPPO include a reduced or fixed population, limited operational cost, and low member participation.